Occurrence of Resolutive Condition of a Deed as a Juridical Fact in Civil Law of Ukraine - KOSTRUBA, Anatoliy V. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
Resolutive condition of a deed was researched in this article. It is a particular circumstance of reality which occurrence terminates rights. Simultaneously this circumstance may not depend on will of the parties of a deed. Therefore it’s not the circumstance which should be deemed a resolutive condition but the fact of its occurrence. It’s the fact of occurrence of particular condition, performance of act, occurrence of certain phenomenon, which is a finishing point in shaping process, existence or termination of such phenomenon. Termination of a law in deeds with resolutive condition is juridical consequence in form of occurrence of resolutive condition. Essence of resolutive condition would mean that it is obligatory to be reflected in each and every civil legal agreement or in a particular group of agreements. Therefore, considering above mentioned information a conclusion may be drawn that resolutive condition in a deed is a concept used by its parties exclusively on their free will. Its distinctive feature is a temporal separation of moment when deed is made or amendments are implemented as well as when it is terminated. Generally, it can be stated that occurrence of resolutive condition of a deed is juridical fact terminating right with suspensive mechanism of action. In such case, a mechanism to terminate right of civil proprietary relations works as ‘delayed bomb’. It is nature of such deed which stipulates that circumstance that there is a particular period of time between a moment when it is made and when its consequences occur. For proper functioning of respective mechanism to terminate right the deed itself ought to meet all necessary requirements regarding its validity foreseen by regulations of civil legislation of Ukraine. Otherwise, such deed becomes defective which may affect functioning of the mechanism of legal settlement of civil proprietary relations.